Answer:
![x1=(-2+√(26/3))/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bgdlal76ucsaev443g8f37yk5d37is0jth.png)
![x2=(-2-√(26/3) )/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sglbvg21zh45n4e98k770kcfvwfjfd9ise.png)
Explanation:
To find the zeros of the quadratic function f(x)=6x^2 + 12x – 7 we need to factorize the polynomial.
To do so, we need to use the quadratic formula, which states that the solution to any equation of the form ax^2 + bx + c = 0 is:
![x=\frac{-b±\sqrt{b^(2)-4ac}}{2a}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yg9i0zgh1x6q3mfaouvp8q5e9uzdlts9eg.png)
So, the first thing we're going to do is divide the whole function by 6:
6x^2 + 12x – 7 = 0 -> x^2 + 2x - 7/6
This step is optional, but it makes things quite easier.
Then we using the quadratic formula, where:
a=1, b= 2, c = -7/6.
Then:
![x=\frac{-2±\sqrt{2^(2)-4(1)(-7/6)}}{2}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fcdz3z83t98rgw4agbjmikayexox3cho27.png)
![x=(-2±√(4 +14/3))/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mjvlwvpmszk9kl12h4yc4mz65dgkfa4kjn.png)
![x=(-2±√(26/3))/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/51bxyqnnsptm3uhtkm5v31fxkaxh3cy3bx.png)
So the zeros are:
![x1=(-2+√(26/3))/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bgdlal76ucsaev443g8f37yk5d37is0jth.png)
![x2=(-2-√(26/3))/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lxjt12a6zk3sojljp4o4xamgygix03p1wh.png)